Property tuning of poly(lactic acid)/cellulose bio-composites through blending with modified ethylene-vinyl acetate copolymer - Pracella, Mariano (2016)
The effect of addition of an ethylene-vinyl acetate copolymer modified with glycidyl methacrylate (EVA-GMA) on the structure and properties of poly(lactic acid) (PLA) composites with cellulose micro fibres (CF) was investigated. Binary (PLA/CF) and ternary (PLA/EVA-GMA/CF) composites obtained by melt mixing in Brabender mixer were analysed by SEM, POM, WAXS, DSC, TGA and tensile tests. The miscibility and morphology of PLA/EVA-GMA blends were first examined as a function of composition: a large rise of PLA spherulite growth rate in the blends was discovered with increasing the EVA-GMA content (0-30 wt%) in the isothermal crystallization both from the melt and the solid state. PLA/EVA-GMA/CF ternary composites displayed improved adhesion and dispersion of fibres into the matrix as compared to PLA/CF system. Marked changes of thermodynamic and tensile parameters, as elastic modulus, strength and elongation at break were observed for the composites, depending on blend composition, polymer miscibility and fibre-matrix chemical interactions at the interface.